2017
DOI: 10.1080/09593330.2017.1411397
|View full text |Cite
|
Sign up to set email alerts
|

Development of α- and γ-Fe2O3decorated graphene oxides for glyphosate removal from water

Abstract: In this study, the proposed adsorbent composed of graphene oxide (GO) functionalized by magnetic nanoparticles of iron oxide (α-γ-FeO) was obtained by a simple ultrasonication process. This new material was used for the removal of glyphosate in water. The nanoparticulated iron oxide used was synthesized by means of a modified sol-gel method, which does not use organic solvents. The adsorbent material (GO-α-γ-FeO) obtained was characterized by magnetic measurements, and it can be proved that it has superparamag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 116 publications
1
16
0
Order By: Relevance
“…XRD analysis revealed the formation of a crystalline structure in the NPFe (Figure B). Peaks at 2θ values close to 28.0, 32.7, 40.0, 52.8, and 58.3° corresponded to the (012), (104), (113), (116), and (018) crystallographic planes characteristic of hematite (α-Fe 2 O 3 , JCPDS code 882359), confirming the synthesis of hematite nanoparticles from FeCl 3 and T. harzianum.…”
Section: Resultsmentioning
confidence: 65%
“…XRD analysis revealed the formation of a crystalline structure in the NPFe (Figure B). Peaks at 2θ values close to 28.0, 32.7, 40.0, 52.8, and 58.3° corresponded to the (012), (104), (113), (116), and (018) crystallographic planes characteristic of hematite (α-Fe 2 O 3 , JCPDS code 882359), confirming the synthesis of hematite nanoparticles from FeCl 3 and T. harzianum.…”
Section: Resultsmentioning
confidence: 65%
“…XRD analysis of this study revealed the small size (17.78 nm) and crystalline nature of mycosynthesized NPs. Previous studies have proved that the small size and crystalline nature of NPs provide them strong antimicrobial properties (Santos et al, 2019). Nanoparticles with small size (5–20 nm) work as excellent antimicrobial agents (Hoag et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Methods of glyphosate removal currently include chemical precipitation (Liu et al 2013), advanced oxidation (Lan et al 2016;Xing et al 2018), membrane filtration (Song et al 2013), biodegradation (Loperena et al 2007), and physical adsorption (Zhou et al 2017;Santos et al 2017;Guo et al 2018;Zavareh et al 2018). Glyphosate adsorption to resins (Zhou et al 2017), graphene oxides (Santos et al 2017), starch (Guo et al 2018), and zeolites (Zavareh et al 2018) has been investigated. Removal methods involving physical adsorption are generally efficient and more environmentally friendly (Zhou et al 2017); however, because these methods are generally based on electrostatic attractions between the substrate and the herbicide, adsorption is highly affected by the solution composition.…”
Section: Introductionmentioning
confidence: 99%